Struktur, Komposisi dan Pertumbuhan Vegetasi pada Lahan Gambut Bekas Terbakar Tahun 2015 Di UPT Laboratorium Alam Hutan Gambut Sebangau: Structure, Composition and Vegetation Growth on Peat Land Used By Fire In 2015 At UPT Natural Laboratory Of Sebangau Peat Forest - Canra P. Lumban Gaol; Wahyudi Wahyudi; Santosa Yulianto (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
This study aims to determine the structure, composition and growth of vegetation on peatlands burned in 2015 in the Natural Laboratory of Peat Forest (LAHG) Sebangau. The benefit of the research is to provide information on the structure, composition and growth of burned peat forest vegetation.Data retrieval using the checkered line method. Determination of the path with the technique of